1998
DOI: 10.1007/s004010050901
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding epidermal growth factor-like growth factor stimulates mitogenic signaling and is highly expressed in human malignant gliomas

Abstract: We previously reported that schwannoma-derived growth factor (SDGF), a member of heparin-binding epidermal growth factor (EGF) family, participates in autocrine pathways and promotes rat glioma cell growth. To investigate the potential role of similar molecules in human gliomas, we examined 7 human glioma cell lines and 11 glioblastoma specimens for expression of the human homologue of SDGF, amphiregulin (AR), as well as heparin-binding EGF-like growth factor (HB-EGF). Northern blot analysis revealed that only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…(45)(46)(47) Furthermore, in vitro experiments have shown that addition of an anti-HB-EGF blocking antibody to human glioblastoma cells reduces proliferation by 30 -40% compared with the addition of normal goat IgG. (48) Inhibition of HB-EGF expression in myeloma cells with CRM197 or an anti-HB-EGF antibody results in the suppression of cell proliferation and induction of cell apoptosis. (49) We recently showed that expression of HB-EGF is critical for cell proliferation of human ovarian cancer cells in nude mice.…”
Section: Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…(45)(46)(47) Furthermore, in vitro experiments have shown that addition of an anti-HB-EGF blocking antibody to human glioblastoma cells reduces proliferation by 30 -40% compared with the addition of normal goat IgG. (48) Inhibition of HB-EGF expression in myeloma cells with CRM197 or an anti-HB-EGF antibody results in the suppression of cell proliferation and induction of cell apoptosis. (49) We recently showed that expression of HB-EGF is critical for cell proliferation of human ovarian cancer cells in nude mice.…”
Section: Cell Proliferationmentioning
confidence: 99%
“…There is growing evidence of increased HB-EGF expression in tumors, including pancreatic, liver, esophageal, melanoma, colon, gastric, ovarian and bladder cancers as well as glioblastoma, compared with normal tissues (6,11,48,63,64) (S . Miyamoto et al, unpublished observation, 2005).…”
Section: Expression Of Hb-egf In Human Cancersmentioning
confidence: 99%
“…22,23 On the other hand, glioblastomas expressing the wild-type EGFR with or without amplification proliferate in paracrine and/or autocrine pathway through the ligand-dependent EGF signaling. 23,24 Astrocytic tumors are known to express the EGFR ligands, ie, EGF, TGF-␣, and HB-EGF, as well as EGFR, 23,24 and HB-EGF plays a key role in the EGFR signals in glioma cells. 24 Because HB-EGF is synthesized as a membrane-anchored proform and processed to soluble active forms that function by binding to EGFR, ectodomain shedding is one of the key regulation steps for the activity of HB-EGF.…”
Section: -21mentioning
confidence: 99%
“…17 This hypothesis is supported by the following data: 1) The EGFR gene is amplified in 30 to 40% of glioblastomas 18 and approximately half of the glioblastomas with the EGFR amplification show genomic rearrangements of the EGFR gene, resulting in the expression of a truncated receptor 19 -21 that is constitutively active without binding to the ligand; 22,23 2) glioblastomas express the EGFR ligands, ie, EGF, TGF-␣, and HB-EGF, 23,24 and EGFR and HB-EGF are co-expressed in the human glioblastomas; 24 and 3) glioma cell proliferation is promoted by the addition of HB-EGF and suppressed by the treatment with anti-HB-EGF blocking antibodies. 24 Several proteinases including ADAM9 12 and ADAM12 13,25 are known to process proHB-EGF to soluble, active HB-EGF. However, no studies have been performed so far to elucidate the relationship between the ADAM expression and HB-EGF shedding in human glioma tissues.…”
mentioning
confidence: 97%
“…[10][11][12] In addition, heparin-binding EGF-like growth factor (HB-EGF) has been found to be overexpressed in most human glioblastoma tissues. 13 As HB-EGF is known to promote cell-motility in wound-healing models, 7 it is reasonable to hypothesize that gliomaderived HB-EGF also influences EGFR-mediated glioma motility.…”
mentioning
confidence: 99%